Insights Into the Structure-Function Relationships of Dimeric C3d Fragments - Wahid, Ayla A.; Dunphy, Rhys W.; Macpherson, Alex; Gibson, Beth G.; Kulik, Liudmila; Whale, Kevin; Back, Catherine; Hallam, Thomas M.; Alkhawaja, Bayan; Martin, Rebecca L.; Meschede, Ingrid; Laabei, Maisem; et al. (Frontiers in Immunology, 2021)
Cleavage of C3 to C3a and C3b plays a central role in the generation of complement-mediated defences. Although the thioester-mediated surface deposition of C3b has been well-studied, fluid-phase dimers of C3 fragments remain largely unexplored. Here we show C3 cleavage results in the spontaneous formation of C3b dimers and present the first X-ray crystal structure of a disulphide-linked human C3d dimer. Binding studies reveal these dimers are capable of crosslinking complement receptor 2 and preliminary cell-based analyses suggest they could modulate B cell activation to influence tolerogenic pathways. Altogether, insights into the physiologically-relevant functions of C3d(g) dimers gained from our findings will pave the way to enhancing our understanding surrounding the importance of complement in the fluid phase and could inform the design of novel therapies for immune system disorders in the future.